A Seminar on Music Research in Higher Education and the Flipped Classroom: An Action Research Project - Capistrán-Gracia, Raúl Wenceslao (2025)
Introduction. The compulsory Seminars on Music Research I and II in the Bachelor of Music program at the Autonomous University of Aguascalientes (UAA) aim to introduce students to the field of research. However, the methods instructors employed have not fully met expectations in terms of engaging students and promoting their active participation in class activities and assignments. Researchers implemented the Flipped Classroom (FC) to explore alternative pedagogical strategies and help students approach music research methods more effectively. Objective. This study aimed to examine the feasibility of implementing FC in the Music Research Seminar I and the benefits and challenges for both instructors and students. Methodology. The methodology used was action research. Data collection methods included a field diary, non-participant and participant observations, and feedback from a critical friend. An ad hoc survey was designed to evaluate the overall intervention and assess the achievement of the study’s objective. Results. The FC approach enabled students to develop a deeper understanding of research methods and tools in music, exchange ideas and questions, and foster a collaborative environment among students and the instructor. The most notable outcome was students’ perception that they could manage their time and work at their own pace. Conclusion. The FC pedagogical strategy proved to be an effective approach for fostering students’ interest in the class, developing their music research skills, and enhancing their metacognitive abilities. Finally, students need time to adapt to a new learning structure and estimate its benefits. Future research could explore the long-term impact of implementing FC and compare teaching approaches to adapt them to students’ learning needs.